2016
DOI: 10.1158/1078-0432.ccr-15-3117
|View full text |Cite
|
Sign up to set email alerts
|

BATON-CRC: A Phase II Randomized Trial Comparing Tivozanib Plus mFOLFOX6 with Bevacizumab Plus mFOLFOX6 in Stage IV Metastatic Colorectal Cancer

Abstract: The efficacy of tivozanib/mFOLFOX6 was comparable with but not superior to bevacizumab/mFOLFOX6 in patients with previously untreated mCRC. Since data from the prespecified interim analysis did not demonstrate superiority, this resulted in discontinuation of the study. The safety and tolerability profile of tivozanib/mFOLFOX6 was consistent with other tivozanib trials. NRP-1 is a potential predictive biomarker for tivozanib activity, but these results require further validation. Clin Cancer Res; 22(20); 5058-6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In the present study, the median PFS, median OS, median TTF and overall RR in the CapeOX plus bevacizumab group were 8.0 months, 22.5 months, 5.8 months and 42.1%, respectively. Several previous prospective studies reported that median PFS, median OS, and overall RR of the CapeOX plus bevacizumab regimen without intermittent oxaliplatin treatment were 9.6-10.0 months, 23.2-34.6 months, 6.7 days and 52.2-59.3%, respectively (Hurwitz et al 2012;Yalcin et al 2013;Uchima et al 2014;Benson et al 2016;Ogata et al 2016). The median PFS and median OS, median TTF and overall RR by CapeOX plus bevacizumab regimen with intermittent oxaliplatin treatment in the present study was slightly worse than those of the CapeOX plus bevacizumab regimen without intermittent oxaliplatin treatment in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the median PFS, median OS, median TTF and overall RR in the CapeOX plus bevacizumab group were 8.0 months, 22.5 months, 5.8 months and 42.1%, respectively. Several previous prospective studies reported that median PFS, median OS, and overall RR of the CapeOX plus bevacizumab regimen without intermittent oxaliplatin treatment were 9.6-10.0 months, 23.2-34.6 months, 6.7 days and 52.2-59.3%, respectively (Hurwitz et al 2012;Yalcin et al 2013;Uchima et al 2014;Benson et al 2016;Ogata et al 2016). The median PFS and median OS, median TTF and overall RR by CapeOX plus bevacizumab regimen with intermittent oxaliplatin treatment in the present study was slightly worse than those of the CapeOX plus bevacizumab regimen without intermittent oxaliplatin treatment in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Tivozanib activity has been also investigated in hepatocellular carcinoma in association with durvalumab [78] and in recurrent, platinum-resistant ovarian cancer, fallopian tube cancer, and primary peritoneal cancer [79,80]. Tivozanib has been studied in phase I and II clinical trials as monotherapy and in combination with other drugs for the treatment of STS [81], glioblastoma [82], breast [83], and colorectal cancers, and other advanced gastrointestinal cancers [84,85].…”
Section: Tivozanibmentioning
confidence: 99%
“…47 Further clinical studies showed that NRP-1 was predictive for the RTKi tivozanib and bevacizumab in a Phase II trial of metastatic colorectal cancer. 48 Tumour microvessel density has also been explored as a potential predictive biomarker for bevacizumab response in a recent randomised control trial of ovarian cancer patients. 49 Patients who displayed higher pre-treatment tumour microvessel density gained a significant PFS benefit from the addition of bevacizumab to standard chemotherapy, in comparison with patients with low microvessel density.…”
Section: Vegf Biologymentioning
confidence: 99%